2005
DOI: 10.2460/ajvr.2005.66.910
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endocrine responses to treatment with deslorelin acetate implants in ferrets with adrenocortical disease

Abstract: In ferrets with ACD, a slow-release deslorelin implant appears promising as a treatment to temporarily eliminate clinical signs and decrease plasma steroid hormone concentrations. Deslorelin may not decrease adrenal tumor growth in some treated ferrets. Deslorelin implants may be useful in the long-term management of hormone-induced sequelae in ferrets with ACD and in treatment of animals that are considered at surgical or anesthetic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 12 publications
2
30
0
11
Order By: Relevance
“…Rosenthal and Peterson, 1996). Some of these hormones might have an effect on the behaviour of the affected ferret and it is mentioned that ferrets with hyperadrenocorticism are indeed more aggressive and that these symptoms can be decreased by using a GnRH agonist (Wagner et al, 2005). In some other species, androstenedione is also considered to elevate aggressive behaviour (Swiss-Webster mice: Luttge and Hall, 1973;golden hamster: Payne, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Rosenthal and Peterson, 1996). Some of these hormones might have an effect on the behaviour of the affected ferret and it is mentioned that ferrets with hyperadrenocorticism are indeed more aggressive and that these symptoms can be decreased by using a GnRH agonist (Wagner et al, 2005). In some other species, androstenedione is also considered to elevate aggressive behaviour (Swiss-Webster mice: Luttge and Hall, 1973;golden hamster: Payne, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…93 A single implant appears to have a significant increase in duration of effect over leuprolide acetate treatment; however, similarly to leuprolide acetate, it does not seem to deter tumor growth or metastasis. 94 Although currently only labeled for ferrets in the United States for ACD, the 4.7-mg implant has also been evaluated to assess contraceptive efficacy. Plasma follicle-stimulating hormone and testosterone concentrations, size of testicles, and spermatogenesis were all suppressed after the use of a deslorelin implant in male ferrets.…”
Section: Other Drugs _______________________________ Deslorelin Acetatementioning
confidence: 99%
“…This study described that deslorelin significantly reduced serum concentrations of 17 beta-estradiol and progesterone as compared with untreated cows. Wagner et al (2005) reported a study in which 15 ferrets with NHA were subcutaneously treated with a single 3-mg implant of deslorelin acetate. Compared with findings before treatment, vulvar swelling and pruritus were reduced or eliminated completely within two weeks after implant insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenocortical disease has been recognized for almost 20 years as a common disease affecting pet ferrets in the US and in European countries (Hillyer, 1992;Lipman et al, 1993;Rosenthal et al, 1993;Rosenthal, 1997;Weiss and Scott, 1997;Wheler and Kamieniecki, 1998;Weiss et al, 1999;Schoemaker et al, 2000Schoemaker et al, , 2002Schoemaker et al, , 2004Wagner et al, 2001Wagner et al, , 2005Schoemaker, 2003;Bielinska et al, 2006). It has been supposed that competent cells in the ferret adrenal cortex undergo neoplastic transformation and adopt features of gonadal steroidogenic cells in response to the hormonal changes that follow gonadectomy.…”
mentioning
confidence: 99%